Validity of Naked Eye Single Tube Red Cell Osmotic Fragility Test for the Diagnosis of β-Thalassemia –A Case Control Study (TAJ: Journal of Teachers Association, 2011)
This study was conducted at the department of paediatrics, Rajshahi Medical College Hospital over a period of 2 years to see the sensitivity, specificity, positive predictive value and negative predictive value of Naked Eye Single Tube Red cell Osmotic Fragility (NESTROF) test for the diagnosis of β-thalassemia. Fifty eight children with β- thalassemia were taken as case and 58 children were taken as control. Among the control 29 children were normal (without anaemia) and 29 children had anaemia other than β-thalassemia. Hemoglobin electrophoresis was done to all children to enroll them as case or control. Then NESTROF test was performed in all cases and controls. The data was analyzed by SPSS V.12. This study showed that sensitivity, specificity, positive and negative predictive value of NESTROF test was 96.55%, 72.41%, 77.77% and 95.45% respectively.TAJ 2011; 24(1): 1-5